Restorative Justice in Drug Crimes Involving Children in Indonesia - Zulhija Yanti Nasution; Muhammad Irsan Barus; Salman Paris Harahap; Abdulroman Mahae (Jurnal Kajian Gender dan Anak, 2026)
This research aims to analyze the restorative justice approach in drug crimes involving children in Indonesia. The research method used a systematic literature review of 11 selected articles. The results showed that restorative justice in cases where children are involved in drugs can be carried out under the condition that the criminal sanction is less than seven years and the child is a first-time offender, whether the child is less than 12 years old or 12-17 years old. The restorative justice approach involves all parties. In cases where the restorative justice approach cannot be used, imprisonment is the final option.